Profile of Superficial Mycoses in Pediatric Dermatology Patient - Maria Ulfa Sheilaadji; Iskandar Zulkarnain (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Superficial mycoses in children is a fungal infection of the skin, hair and nails that affected children aged 14 years and below. The superficial mycoses common in children are tinea capitis, pityriasis versicolor and diaper candidiasis. Purpose: To evaluate the distribution of superficial mycoses in pediatric patients in Pediatric Dermatology Division of Dermatology and Venereology Outpatient Clinic in Dr. Soetomo General Hospital Surabaya. Methods: Retrospective study using new patient’s medical record during the period of January 1 2013 until December 31 2015. Results: In period year 2013-2015 the total new superficial mycoses’s pediatric patients is 320 with the precentage in 2013 is 0.4%, in 2014 is 0.5%, and in 2015 is 0.4%. The proportion in male is more than female, and most frequent at aged 5-14 that 54.6%. Most common complain is itchy with the most common diagnosed is pitiriasis versicolor 28.3%. Potasium hydroxide is the most common additional examination in 70.3% and frequent use therapies are ketoconazole and griseofulvin orally. Conclusion: Superficial mycoses especially pitiriasis versicolor in pediatric is still a common issues in Indonesia, specially in Surabaya.